High Temperature Ultrasonic Transducers: A Review - Rymantas Kazys; Vaida Vaskeliene (Sensors, 2021)
There are many fields such as online monitoring of manufacturing processes, non-destructive testing in nuclear plants, or corrosion rate monitoring techniques of steel pipes in which measurements must be performed at elevated temperatures. For that high temperature ultrasonic transducers are necessary. In the presented paper, a literature review on the main types of such transducers, piezoelectric materials, backings, and the bonding techniques of transducers elements suitable for high temperatures, is presented. In this review, the main focus is on ultrasonic transducers with piezoelectric elements suitable for operation at temperatures higher than of the most commercially available transducers, i.e., 150 °C. The main types of the ultrasonic transducers that are discussed are the transducers with thin protectors, which may serve as matching layers, transducers with high temperature delay lines, wedges, and waveguide type transducers. The piezoelectric materials suitable for high temperature applications such as aluminum nitride, lithium niobate, gallium orthophosphate, bismuth titanate, oxyborate crystals, lead metaniobate, and other piezoceramics are analyzed. Bonding techniques used for joining of the transducer elements such as joining with glue, soldering, brazing, dry contact, and diffusion bonding are discussed. Special attention is paid to efficient diffusion and thermo-sonic diffusion bonding techniques. Various types of backings necessary for improving a bandwidth and to obtain a short pulse response are described.